2014
DOI: 10.3109/09637486.2014.898258
|View full text |Cite
|
Sign up to set email alerts
|

New criteria for supplementation of selected micronutrients in the era of nutrigenetics and nutrigenomics

Abstract: Advances in molecular biology, emergence of novel techniques and huge amount of information generated in the post-Human Genome Project era have fostered the emergence of new disciplines in the field of nutritional research: Nutrigenomics deals with the effect of diet on gene expression whereas nutrigenetics refers to the impact of inherited traits on the response to a specific dietary pattern, functional food or supplement. Understanding the role of micronutrient supplementation with specific genetic backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 100 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Recently, genetic variations of haptoglobin, polymorphisms in the transporters of AA, and deleted polymorphisms of glutathione- S -transferase have provided genetic information regarding possible relative AA levels [ 25 , 26 , 27 ].…”
Section: Ascorbic Acid Epigenetic Modulation and Nutrigenomicsmentioning
confidence: 99%
“…Recently, genetic variations of haptoglobin, polymorphisms in the transporters of AA, and deleted polymorphisms of glutathione- S -transferase have provided genetic information regarding possible relative AA levels [ 25 , 26 , 27 ].…”
Section: Ascorbic Acid Epigenetic Modulation and Nutrigenomicsmentioning
confidence: 99%
“…Genomic sequencing can provide insight into a vast array of health-related information, from susceptibility to infection [ 65 ] to responses to dietary choices [ 66 ] to geographic ancestry [ 67 ]. Its most common current uses, however, are to identify and diagnose disease, and to inform treatment selections.…”
Section: The Utility and Cost-effectiveness Of Genomic Sequencingmentioning
confidence: 99%
“…Conversely, the risk of deficiency for carriers of the Hp1 allele (Hp2-1 + Hp1-1 phenotype) was lower and not significant (OR = 1.69, 95% CI = 0.80-3.63) after adjusting for BMI, sex, energy intake, use of oral contraceptives, C-reactive protein levels, plasma α-tocopherol, ethnicity, and season (16). Based on this evidence, Schwartz (46) concluded that the required daily vitamin C intake in Hp 2-2 individuals should be higher than other Hp phenotypes.…”
Section: Genetic Variations and Vitamin C Statusmentioning
confidence: 90%